Optimalisasi Return Deposito Mudharabah Di Bank Umum Syariah - Faulia Anggeraini; Inda Arfa Syera (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2021)
The main objective of this study is to determine the effect of return on assets and operating costs of income on the return on profit sharing from mudharabah deposits in Islamic commercial banks. The population and sample in this study are Islamic Banking Statistics (SPS) data, which includes statistics on Return on Assets, Operating Costs of Operational Income, and return on profit sharing from mudharabah deposits for Islamic Commercial Banks from January 2016 to December 2019. The results show that partial and simultaneous return on assets and operating costs of operating income have a positive and significant effect on return for the results of mudharabah deposits for Islamic Commercial Banks. However, the most dominant variable that has the greatest influence in this study is the operational cost of operating income.